2019
DOI: 10.1371/journal.pone.0214755
|View full text |Cite
|
Sign up to set email alerts
|

Sero-prevalence and trends of transfusion-transmissible infections among blood donors at Bahir Dar district blood bank, northwest Ethiopia: A four year retrospective study

Abstract: Background Blood transfusion is an effective treatment for saving millions of lives even though transfusion- transmissible infections are the major problem. Therefore, the aim of this study was to assess the sero-prevalence and trend of transfusion-transmissible infections among blood donors. Methods A retrospective study was conducted form July 2014 to June 2018 at Bahir Dar district blood bank. Descriptive statistics was presented using percentages, medians and interq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
29
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 21 publications
14
29
8
Order By: Relevance
“…Sex was also found to be associated with prevalence of TTIs, the prevalence was found to be higher in males. A study conducted in Bahir Dar had published similar finding [ 9 ].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Sex was also found to be associated with prevalence of TTIs, the prevalence was found to be higher in males. A study conducted in Bahir Dar had published similar finding [ 9 ].…”
Section: Discussionsupporting
confidence: 64%
“…Similarly, a study conducted in Harari, also documented that old age was associated with higher probability of having Treponema pallidum compared to younger age [ 14 ]. Another study done in Bahir Dar had also showed that old age was again associated with prevalence of HBV in blood donor [ 9 ]. Evidence from Eretria and Tanzania also support association of age and sero positivity of TTIs [ 6 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data show that there is a direct correlation between the economic condition of countries and TTI incidence. Those countries with higher income can more easily provide preventive and vaccination programs for their people than countries with lower income [11,12]. Education is another important factor that can significantly decrease the rate of TTIs among blood donors, mostly by reducing risky behaviors [13].…”
Section: Discussionmentioning
confidence: 99%
“…5 The economic cost of failure to control the transmission of the infections includes increased requirements of medical care, high level of dependency and heavy burden on already overstretched health and social services on national economy. [6][7][8] Acquisition of infections during the window period from the blood donors can be a serious threat to the safety of collected blood which is transfused to the recipient. These TTIs can cause prolonged viremia also causes fatal chronic or life threatening disorders.…”
Section: Introductionmentioning
confidence: 99%